Infark Miokard pada Pasien dengan Infeksi HIV: Laporan Kasus: Laporan Kasus - Sakina, Adriani; Rahmah, Fitri (Cermin Dunia Kedokteran, 2026)
Introduction: The association of myocardial infarction and HIV infection is influenced by many risk factors, either the specific risk factors of cardiovascular and metabolic disease, or HIV-related risk factors related to the immunologic process and the effects of antiretrovirals (ARV). Case: A 43-year-old man on ARV therapy presented with chest pain as heaviness under the left breastbone and referred to the shoulder to the back for 24 hours. The ECG showed ST-segment elevation in leads II, III, and aVF. The patient underwent intensive cardiac care and receivedaspirin therapy with a loading dose of 160 mg, followed by a maintenance dose of 80 mg daily, clopidogrel therapy with a loading dose of 300 mg, followed by a maintenance dose of 75 mg daily, and intravenous anticoagulant enoxaparin injection therapy, 75 mg twice daily. Thepatient also finally stopped smoking. Discussion: Myocardial infarction in people with HIV is a multifactorial condition influenced by various risk factors, chronic inflammation associated with HIV, endothelial dysfunction, and the effects of certain ARV therapies. The combination of tenofovir-based ARVs and efavirenz has not been shown to increase the risk of myocardial infarction and even has a protective effect on lipid profiles. Conclusion: In general, management of myocardial infarction in HIV-infected patients did not differ from that of general population;one important issue being the drug interaction of ARV with antiplatelet agents and statins. The prognosis of HIV-infected patients who had myocardial infarction did not differ from that of those without. However, acute myocardial infarction recurrence in the HIV-infected population is higher than general population.